179 Clinical Outcomes From a Single-Site Phase I Study of Neural Stem Cell Transplantation for Chronic Spinal Cord Injury. (1st April 2022) - Martin, Joel; Curtis, Erik; Cleary, Daniel; Mendoza, Michelle; Jamieson, Catriona; Marsala, Martin; Ciacci, Joseph D.
Abstract : INTRODUCTION: We previously reported safe implantation and improvement in motor and sensory scores using neural stem cell line (NSC) NSI-566 in chronic thoracic complete spinal cord injury (SCI) patients. METHODS: A total of four subjects received NSI-566 spinal cord implantation. All subjects tolerated the procedure well with no serious adverse events in the immediate post-procedure period. Prospective data have been collected including ISNCSCI scores, functional and pain surveys, SCIM scores, electromyography (EMG), Brain Motor Control Assessment (BMCA), and serial MRI. RESULTS: Two patients experienced improvements in neurological level of injury (NLI), motor score, and sensory score. BMCA showed newly developed muscle responsiveness in lower limbs to reinforcement maneuvers in one patient. Three subjects experienced new EMG activity in lower muscle groups. Two patients had overall decreased pain scores post-operatively, which included both discomfort and allodynia in the transition zone, surgical site pain, and neuropathic and nociceptive pain elsewhere. MR imaging showed no radiographical evidence of immediate or delayed complications after the stem cell injections. CONCLUSION: Our current clinical data demonstrate that spinal grafting of the human NSI-566 cell line in chronic spinal trauma patients is safe with no detectable side effects identified at 60 months after cell delivery. Despite the small sample size, the key strengths of the study are the extensive follow-up period and the timeline of treatment. Like other Phase I studies, this study was intended to provide proof of safety and tolerability and proof of concept data that will justify the next cohort.